Proyecto de electrificación rural vereda Bella Ena, Pivijay Magdalena (2008)
The lack of electricity for a zone or population can be a determinant factor in the quality of life with which they count its inhabitants, for these places where the farming industry this seeking to arise is done necessary to include this resource to support the plans of improvement and development that the governmental entities propose. They based on said need should develop studies that tend the benefit of the community and the extension in the national territory of the advantages that can obtain the populations if include the home public utilities. The following project contains results and memories of mechanical and electric calculations, based on the analysis for the rural electrification of the path Bella Ena located in the municipality of Pivijay in the department of the Magdalena; the path conformed by peasants belonging to a cooperative one multiactiva of palmicultores counts on a high potential one for the sowing of palm, said potential is seen affected by the lack of electric power among others. This project is focused to carry out the pertinent studies that permit to the community mentioned to include the electric power, for the residential use and industrial farming and in this manner to improve or quality of life. As it contribute on the part of the investigators the attainment of the cartographic, technical, and theoretical bases for the construction of the networks of average tension can be concluded, budgets of design, information of labor and materials required. And of general form to reflect on the need to motivate to future generations for they be interested in developing projects and studies that benefit the communities that fight besides leaving the problems that current mind lives the country.